1986
DOI: 10.1001/archinte.146.1.145
|View full text |Cite
|
Sign up to set email alerts
|

Environmental illness. A clinical review of 50 cases

Abstract: A review of 50 patients with a clinical ecology diagnosis of environmentally induced illness is reported. Histories were extremely heterogeneous. Eight patients had no symptoms or disease, 11 had symptoms caused by preexisting nonenvironmental disease, and 31 had multiple subjective symptoms. No consistent physical findings or laboratory abnormalities were found. Serum levels of immunoglobulins and complement, and circulating lymphocyte, B-cell, T-cell, and T-cell subset counts were not significantly abnormal.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
52
1
2

Year Published

1986
1986
1999
1999

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(56 citation statements)
references
References 10 publications
1
52
1
2
Order By: Relevance
“…Several researchers believe that MCS is a manifestation of traditional psychiatric disorciers such as depression, anxiety and somatization disorden andior that MCS develops in individuals with predisposing psychiatric conditions (Black, Terr, 1986). Case histories, psychiatric and psychologicd measurement techniques, and medical assessments have al1 k e n used to examine psychopathology in MCS.…”
Section: Psychogenic Ineoriesmentioning
confidence: 99%
See 4 more Smart Citations
“…Several researchers believe that MCS is a manifestation of traditional psychiatric disorciers such as depression, anxiety and somatization disorden andior that MCS develops in individuals with predisposing psychiatric conditions (Black, Terr, 1986). Case histories, psychiatric and psychologicd measurement techniques, and medical assessments have al1 k e n used to examine psychopathology in MCS.…”
Section: Psychogenic Ineoriesmentioning
confidence: 99%
“…Terr (1986) reported that "these patients had clinicat features of hypochondriasis, somatization, conversion hysteria, anxiety, depression and obsessive behavior ... The subgroup of 3 1 patients with multiple symptoms most likely of psychological origin corresponds to the type of patient described repeatedly in the clinical ecology literature."…”
mentioning
confidence: 94%
See 3 more Smart Citations